Effects of sports drink mouth rinse on cycling performance in a warm and humid environment among trained junior cyclists. / Nurhanisah Muhd Khairi ... [et al.] - Muhd Khairi, Nurhanisah; Razlan, Zulkarnain; Yin, Marilyn Ong Li; Che Jusoh, Mohd Rahimi (Universiti Teknologi MARA, 2021)
The carbohydrate-electrolyte mouth rinse has been widely documented as one of the cooling strategies that attenuate the rise in core temperature and subsequently contribute to enhanced exercise performance. However, this is the first study investigating the effects of sports drink mouth rinse (100Plus®) on trained junior cyclists during 15-min time trial performance in the warm-humid environment. This study aimed to investigate whether sports drink mouth-rinse (carbohydrate-electrolytes) conferred performance and thermoregulatory responses benefits while cycling in a hot and humid environment; and whether the timing (pre and during exercise) of rinses was of importance when compared with a control rinsing with plain water only. Eight male Kelantan state junior cyclists ages 17 ± 1.8 years old completed carbohydrate-electrolytes (100Plus®) mouth rinse and control trial (plain water) during the fixed intensity cycling at 55% VO2max for 45-min and 15-min work-dependent self-paced cycling time trial. Each cyclist rinsed his mouth with 25 ml bolus (100Plus®) sports drink or plain water at every 15-min (15,30 and 45-min) for 10-second during the duration of fixed intensity cycling. Heart rate, rectal and skin temperatures, and Borg's rating of perceived exertion (RPE), thermal discomfort and sensation scale were recorded. Results showed that 100Plus® mouth rinse did not improve cycling performance in thermally stress and demonstrated a higher work completed in control (144.7 ± 15.8 kJ) compared to sports drink mouth-rinse (126.2 ± 20.2 kJ) trials. Thus, the most obvious finding from this study was that sports drink mouth-rinse before and during exercise were unable to improve exercise performance in a warm and humid environment.